Answer:
x = 5 , y = -1
Explanation:
x + 2y = 3........(equation 1)
x - y = 6..........(equation 2)
make x the subject of the formula in (equation 1)
x = 3 - 2y
substitute for x in (equation 2)
3x - y = 6
(3- 2y) - y = 6
3 - 2y - y = 6
3 - 3y = 6
-3y = 6 - 3
![( - 3y)/( - 3) = (3)/( - 3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/qv68xo825fza2gs3xyc9tik6pnkuvpfw5r.png)
![y = - 1](https://img.qammunity.org/2022/formulas/mathematics/high-school/jpr1a427hbaky1b62trq4cykzv6u965alx.png)
substitute for y in (equation 1)
x = 3 - 2y
![* = 3 - 2( - 1)](https://img.qammunity.org/2022/formulas/mathematics/high-school/nyv0e1fl13jztbsp1k57c2rc35yd52lexo.png)
x = 5